Histological, physiological, and transcriptomic responses of hepatopancreas to air exposure in asian freshwater clam Corbicula fluminea - Zhang, Ting; Xu, Dongpu; Lv, Guohua; Wang, Anqi; Wen, Haibo (Frontiers in Physiology, 2022)
Corbicula fluminea (C. fluminea) is an important freshwater economy shellfish in China, but it often suffers from air exposure during transportation. In this study, we investigated the histological, physiological (mainly including respiratory metabolism, antioxidant capacity, and immune function), and transcriptomic responses of hepatopancreas in C. fluminea to different times of air exposure. At histological level, air exposure caused vacuolation of digestive cells (24-96 h) and enlargement of digestive tubule lumen (6-96 h) in hepatopancreas. At physiological level, the activities of enzymes related to glycolysis (hexokinase and pyruvate kinase) and anaerobic respiration (lactate dehydrogenase) were increased first (6-24 h) of air exposure, then came back to normal level or even decreased. The activity of aerobic respiration-related enzyme (succinic dehydrogenase) began to reduce from 24 h of air exposure. The activities of antioxidant enzymes (superoxide dismutase and catalase) were enhanced during 6-48 h of air exposure and then returned to control level or even inhibited. The content of malondialdehyde (MDA) increased from 96 h of air exposure. The activities of immune-related enzymes (acid phosphatase and alkaline phosphatase) increased during 6-48 h, then returned to normal or began to decline. At transcriptome level, 44 differentially expressed genes (DEGs) in the hepatopancreas were identified after 96-h air exposure. Among these DEGs, 8 were associated with glycolysis, TCA cycle, immune, and antioxidant, and were downregulated after 96-h air exposure. Taken together, these findings illuminated the response of C. fluminea to air exposure at histological, physiological and transcriptomic levels, which will be beneficial to the aquaculture and transportation of C. fluminea.